Evaluation of usage patterns and user perception of the drug–drug interaction database SFINX. Issue 5 (May 2015) - Andersson, Marine L.; Böttiger, Ylva; Bastholm-Rahmner, Pia; Ovesjö, Marie-Louise; Vég, Aniko; Eiermann, Birgit
Highlights SFINX is used when prescribers and pharmacists meet patients. Information, given by SFINX, results in changes in patient care. Prescribers and pharmacists learn about interactions by using SFINX.